Evidence for bicomponent fibers: A review - Zhu Shufang (De Gruyter, 2021)
Recently, bicomponent fibers have been attracting much attention due to their unique structural characteristics and properties. A common concern was how to characterize a bicomponent fiber. In this review, we generally summarized the classification, structural characteristics, preparation methods of the bicomponent fibers, and focused on the experimental evidence for the identification of bicomponent fibers. Finally, the main challenges and future perspectives of bicomponent fibers and their characterization are provided. We hope that this review will provide readers with a comprehensive understanding of the design and characterization of bicomponent fibers.